Non-linear association between serum spermidine and mild cognitive impairment: Results from a cross-sectional and longitudinal study - Xu, Jiahui; Sun, Zhaoqing; Zhang, Rui; Li, Ruixue; Yu, Zhecong; Zhang, Qianlong; Ma, Yanan; Xing, Fuguo; Zheng, Liqiang (Frontiers in Aging Neuroscience, 2022)
Background: Although animal studies show that spermidine (SPD) affects cognitive function, the relevant evidence among humans is limited. We aim to examine the association between serum spermidine levels and cognitive performance. Methods: We conducted a cross-sectional and longitudinal study including a baseline and one follow-up survey. The baseline survey was conducted from June 2019 to August 2019, while the follow-up survey was conducted from June 2021 to August 2021. We analyzed 3774 adult participants aged >35 years, who had no history of dementia. Results: The mean (SD) age of the participants was 57.4 (9.8) years. Relative to the first tertile, the multivariate-adjusted ORs (95% CIs) of mild cognitive impairment (MCI) for the second and third tertile groups were 0.78 (0.65, 0.93) and 0.80 (0.67, 0.96), respectively. Restricted cubic spline models show that there is a non-linear association between SPD and MCI. In line with cross-sectional findings, the longitudinal study showed that a high SPD concentration may indicate a lower risk of MCI [ORs (95% CIs) for the third tertile of 0.62 (0.39, 0.99)]. Conclusions: Our findings suggest that spermidine is favorable for cognitive function. Monitoring the spermidine levels may help reduce the incidence of MCI, hence decreasing the burden of MCI.